Stable in vivo expression of the cystic fibrosis transmembrane conductance regulator with an adeno-associated virus vector. - Flotte, T R (1993)
Adeno-associated virus (AAV) vectors expressing the normal cystic fibrosis transmembrane conductance regulator (CFTR) cDNA complement the cystic fibrosis (CF) defect in vitro. Unlike other DNA virus vectors, AAV is a stably integrating virus, which could make possible long-term in vivo complementation of the CF defect in the airway epithelium. We report AAV-CFTR gene transfer and expression after infection of primary CF nasal polyp cells and after in vivo delivery of AAV-CFTR vector to one lobe of the rabbit lung through a fiberoptic bronchoscope. In the rabbit, vector DNA could be detected in the infected lobe up to 6 months after administration. A 26-amino acid polypeptide sequence unique to the recombinant AAV-CFTR protein was used to generate both oligonucleotide probes and a polyclonal antibody which allowed the unambiguous identification of vector RNA and CFTR protein expression. With these reagents, CFTR RNA and protein were detected in the airway epithelium of the infected lobe for up to 6 months after vector administration. AAV vectors do, therefore, efficiently promote in vivo gene transfer to the airway epithelium which is stable over several months. These findings indicate that AAV-CFTR vectors could potentially be very useful for gene therapy.